Use of the AFX Stent Graft in Patients with Extremely Narrow Aortic Bifurcation: A Multicenter Retrospective Study. (4th October 2021) - Wagenhäuser, M. U.; Floros, N.; Nikitina, E.; Mulorz, J.; Balzer, K. M.; Goulas, S.; Petrich, M.; Dueppers, P.; Simon, F.; Schelzig, H.; Oberhuber, A.
Abstract : Introduction . This study analyzed the patient outcomes following endovascular aortic aneurysm repair (EVAR) for infrarenal aortic pathologies with very narrow aortic bifurcations using the AFX stent graft. Methods . The data was retrieved from the archived medical records of 35 patients treated for abdominal aortic aneurysm (AAA) (48.6%) or penetrating aortic ulcer (PAU) (51.4%) with very narrow aortic bifurcation between January 2013 and May 2020. Patient survival, freedom from endoleak (EL), and limb occlusion were estimated applying the Kaplan–Meier method. Results . The mean follow-up time was 20.4 ± 22.8 months. The mean aortic bifurcation diameter was 15.8 ± 2.2 mm . Technical success was 100%, and no procedure-related deaths occurred. Two type II ELs occurred within 30-day follow-up. We observed one common iliac artery stenosis at four months and one type III EL at 54 months in the same patient, both of which required re-intervention. Overall patient survival was 95 ± 5 % (AAA: 100%; PAU: 89 ± 10 % ), freedom from limb occlusion was 94 ± 5 % (AAA: 91 ± 9 % ; PAU: 100%), freedom from type II EL was 94 ± 4 % (AAA: 88 ± 8 % ; PAU: 100%), and freedom from EL type III was 83 ± 15 % (AAA: 80 ± 18 % ; PAU: 100%) at the end of the follow-up period. Conclusions . Very narrow aortic bifurcations may predispose patients to procedure-related complications following EVAR. Our results suggest a safe use of the AFX stent graft in such scenarios. The overall short- and long-term procedure-related patient outcomes are satisfying albeit they may seem superior for PAU when compared to AAA.